THE ROLE OF TRUST AND AFFECTIVE IDENTIFICATION AS A MEDIATOR BETWEEN PERCEIVED CSR AND INTENTION - Dewanti, Retno; Pamela, Erina; Mohammad Shah, Khairul Anuar bin (Social Economics and Ecology International Journal, 2017)
This research about CSR was conducted at educational institutions, where the purpose of this study was to evaluate CSR activities. It is known that CSR activities are an obligation from the government to companies. This study examined CSR being perceived by the participants, where the perception influences trust and affective identification that will ultimately have an impact on intention. Intention means a reaction to attend the training which one matching with what the participants need. CSR activities do not only aim to fulfil the responsibility, but the company sincerely provides training to improve the quality of community life. The rresearch uses smartPLS 3.0. and a total of 100 respondents. The results of this study showed a significant relationship between perceived CSR to the trust as well as affective identification. Trust and affective identification showed a successful mediator between perceived CSR and intention.